Keanekaragaman Kelas Crustacea Sub-Kelas Malacostraca pada Ekosistem Mangrove Pantai Padadita Kabupaten Sumba Timur - Aloysius Rivaldi Talo; Anita Tamu Ina (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
The purpose of this study was to determine the diversity of the Crustacea Class Diversity Subclass (Malacostraca) in the mangrove ecosystem of Padadita Beach, East Sumba Regency. The research method used was the quadratic transect and analyzed using a quantitative descriptive approach with the diversity index formula Shannon-Wiener. This study used a sampling technique, namely purposive sampling with a plot size of 2 x 2 meters placed perpendicular to the depth of 200 meters using a plot of 27 plots. The environmental factors measured were temperature, salinity, degree of acidity (pH) and levelsoxygen (DO). Measurements were made at each observation station. The results showed that 5 species of Crustaceans (Malacostraca) that is Gelasimus vocans, Eriphia verrucosa, Ashtoret lunaris, Thalamita stimpsoni and Metopograpsus latifrons. The diversity index obtained is in the moderate category with a value of H’ =1,369.